STABILISASI SEBAGAI BENTUK PENATAAN PKL MAKANAN SIAP SAJI DI KOTA SURAKARTA - Murtanti Jani Rahayu; M Musyawaroh (TATALOKA, 2013)
Management of hawkers has purpose to improve the welfare of hawkers, maintain publicorder, and sanitation. Management of hawkers in the city of Surakarta, which began in 2006, the successful concept of the arrangement is not only seen from the hawkers town aesthetic that hasalways been the main reason, but also improving the quality of performance of the activities afterthe program implemented to ensure sustainability.One of form of arrangement that has been implemented in the city of Surakarta is stabilization. In determining the form of the arrangement,unique character and behavior are very diverse hawkers must be known to ensure that hawkers canreceive the planned arrangement. This paper aims to know determine the efficacy of this form ofstabilization arrangement hawkers particular arrangement was done by first looking at thecharacteristics of hawkers activity. Statistical analysis used to determine the success of the arrangement of the hawkers performance combined with qualitative analysis found that the successof the arrangement hawkers aesthetic form of stabilization in the city is not same with the improved performance / empowerment of hawkers.